Some Geometric Properties of a New Type Metric Space - Cinar, Muhammed; Karakas, Murat; Et, Mikail (Prairie View A & M Univ, Dept Mathematics, 2013)
In this paper, we define a metric on our new space and then show that this linear metric space is k-nearly uniform convex and has property beta where p=(p(k)) is a bounded sequence of positive real numbers. Finally, we give a result about property (H) by using k-nearly uniform convexity.
Keywords: Cesaro difference sequence space; Luxemburg norm; extreme point; convex modular; property (H)